Mapping of Scad Fish (Decapterus sp.) Fishing Grounds Based on the Suitability Level of Oceanographic Parameters in FMA 573 - Simbolon, Domu; Apriela, Huryn Najmi; Taurusman, Am Azbas; Aprianti , Eka (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. Integration of multi-variable oceanographic parameters for mapping fishing areas. 2. Spatial-temporal dynamics based on changes in oceanographic parameters. 3. Development of upwelling index-based fishing area detection methods. 4. Optimization of fishermen's operations through the prediction of potential locations.   Abstract Sustainable management of scad stocks (Decapterus sp.) in FMA 573 necessitates integrating satellite-based oceanographic monitoring to identify distribution zones amid complex aquatic dynamics. This study integrates satellite imagery, descriptive analysis, and spatial modeling to map oceanographic parameters and identify fish distribution zones, aimed at enhancing the monitoring and sustainable management of scad stocks in FMA 573. The research combines satellite-based oceanographic monitoring with CPUE analysis and spatial modeling to determine fish distribution based on environmental suitability. Results indicate that oceanographic conditions fluctuate seasonally, with warm waters dominating the West Monsoon and Transition-1, while higher salinity and Chl-a concentrations characterize the later seasons. Habitat suitability modeling reveals that scad potential is primarily concentrated in coastal areas during the West Monsoon and Transition-1. The spatial distribution of the scad in FMA 573 shows a preference for coastal areas with a strong dependence on oceanographic dynamics. This spatial shift between coastal and offshore zones is primarily driven by the seasonal expansion of optimal SST and Chl-a concentrations, which alter the boundaries of suitable habitats. However, a spatial-temporal discrepancy exists: while environmental suitability peaks early in the year, industrial landing data shows fishing activity concentrated offshore, peak during Transition-2. This mismatch suggests that existing catch data reflects industrial operational habits rather than the full biological potential of nearshore areas, highlighting the need for supplementary data from small-scale fishers to validate coastal PFZs. These findings provide a baseline for predictive catch modeling and seasonal spatial recommendations. Identifying the shift from coastal zones in the West Monsoon to offshore waters in Transition-1 allows for optimized fishing efforts, improved fuel efficiency, and more precise monitoring of fishing pressure.